INDIGENOUS MASTERS AND THEIR SOCIO-EDUCATIONAL EXPERIENCES IN THE PERUVIAN ALTIPLANO IN THE TWENTIETH CENTURY - Henry Mark Vilca Apaza (2018)
At the end of the 19th century important social and educational events took place in Puno-Peru, such as the accelerated trade of wool to the European market, which consequently led to the dispossession of lands from peasant communities by the gamonales taking advantage of illiteracy, and in response to these facts , in the twentieth century, peasant leaders called messengers emerge to demand the State school to educate themselves, and before the opposition of the gamonal found clandestine schools. As a consequence of these struggles, schools were established in rural areas with the policy of incorporating the Indian into "civilization" but with adverse effects on the learning of Spanish that led to the emergence of indigenous teachers to propose a pedagogy contextualized at the time of fighting for the revaluation of the indigenous, whose lives and contributions are visible in the present.